High and rising burden of hip and knee osteoarthritis in the Nordic region, 1990–2015: Findings from the Global Burden of Disease Study 2015 - Aliasghar A Kiadaliri (Acta Orthopaedica, 2018)
Background and purpose — Osteoarthritis (OA) imposes a substantial burden on individuals and societies. We report on the burden of knee and hip OA in the Nordic region. Patients and methods — We used the findings from the 2015 Global Burden of Diseases Study to explore prevalence, years lived with disability (YLDs), and disability-adjusted life-years (DALYs) of OA in the 6 Nordic countries during 1990–2015 (population of about 27 million in 2015). Results — During 1990–2015, the number of prevalent OA cases increased by 43% to 1,507,587 (95% uncertainty interval [UI] 1,454,338–1,564,778) in the region. OA accounted for 1.3% (UI 1.0–1.7) of YLDs in 1990, increasing to 1.6% (UI 1.2–2.0) in 2015. Of 315 causes studied, OA was the 15th leading cause of YLDs, causing 52,661 (UI 34,056–77,499) YLDs in 2015; of these 23% were attributable to high body mass index. The highest relative importance of OA was reported for women aged 65–74 years (8th leading cause of YLDs in 2015). Among the top 30 leading causes of YLDs in the region, OA had the 5th greatest relative increase in total YLDs during 1990–2015. From 1990 to 2015, increase in age-standardized YLDs from OA in the region was slightly lower than increase at the global level (7.5% vs. 10.5%). OA was, however, responsible for a higher proportional burden of DALYs in the region compared with the global level. Interpretation — The OA burden is high and rising in the Nordic region. With population growth, aging, and the obesity epidemic, a substantial rise in the burden of OA is expected and should be addressed in health policies.